2023
DOI: 10.1021/acs.analchem.2c04395
|View full text |Cite
|
Sign up to set email alerts
|

Precision Navigation of Venous Thrombosis Guided by Viscosity-Activatable Near-Infrared Fluorescence

Abstract: Thrombus are blood clots formed by abnormal hemostasis in blood vessels and are closely associated with various diseases such as pulmonary embolism, myocardial infarction and stroke. Early diagnosis and treatment of thrombus is the key to reducing the high risk of thrombotic disease. Given that early thrombus is small in early size, free instability, wide regional distribution and fast formation, it is urgent to develop all-inclusive detection methods that combine high signal-to-noise ratio, in situ dynamic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Among the many CO detection methods, uorescent probes have been widely developed due to their high selectivity, high sensitivity, and real-time imaging. [14][15][16][17][18][19][20][21][22] In 2012, Chang et al constructed the rst uorescent probe for imaging CO in living cells, and since then, the use of uorescent probes for the detection of CO in living cells or in vivo has been a hot topic of research. [23][24][25][26][27][28][29][30] In 2015, Dhara et al reported a novel way to detect CO using the Tsuji-Trost strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many CO detection methods, uorescent probes have been widely developed due to their high selectivity, high sensitivity, and real-time imaging. [14][15][16][17][18][19][20][21][22] In 2012, Chang et al constructed the rst uorescent probe for imaging CO in living cells, and since then, the use of uorescent probes for the detection of CO in living cells or in vivo has been a hot topic of research. [23][24][25][26][27][28][29][30] In 2015, Dhara et al reported a novel way to detect CO using the Tsuji-Trost strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20] Consequently, fluorescent probes have been developed to detect viscosity and SO 2 derivatives in living cells and animals. [21][22][23][24][25][26][27][28][29] Mitochondria, often referred to as the "cellular power house", have a crucial role in cellular physiological processes and signal transduction pathways. They are involved in energy generation, production of reactive oxygen species (ROS), regulation of cell growth and apoptosis, and cell anabolism.…”
Section: Introductionmentioning
confidence: 99%
“…12–20 Consequently, fluorescent probes have been developed to detect viscosity and SO 2 derivatives in living cells and animals. 21–29…”
Section: Introductionmentioning
confidence: 99%
“…In a low-viscosity environment, the probe releases weak fluorescence resulting from the free rotation of rotor-connected single or double bonds, while as viscosity increases their rotation was inhibited by forming a large conjugated system, and result in strong fluorescence in a tall-viscosity environment. , Interestingly, most rhodamine and other fluorophores-based viscosity probes, their rotors are composed of aromatic ring: benzo-indole, polyaniline group, benzo-thiophene, pyridine salt, quinoline, imidazole, azobenzene, etc. (Table S1 in the Supporting Information), , which have relatively a greater size and clumsy structures. As reported, the design principles of viscosity response probes include computed tomography (CT), 6 , aggregation-induced emission (AIE), , photoinduced electron transfer (PET), intramolecular charge transfer (TICT), and fluorescence resonance energy transfer (FRET). , Particularly, TICT is a good strategy for designing viscosity probes, as it can enhance fluorescence emissions through the restriction of intramolecular rotations. , Therefore, designing a NIR small molecule with great properties and TICT mechanism to detect changes in intracellular viscosity is of great importance.…”
Section: Introductionmentioning
confidence: 99%